Development and interdisciplinarity: Re-examining the "economics silo" - Matthias Aistleitner (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2022)
Recent evidence from citation analysis [Mitra, S., Palmer, M, Vuon, V. (2020). Development and interdisciplinarity: A citation analysis. World Development, 135, 105076; hereafter MPV] shows that development as a field of study hardly interacts with other disciplines - except mainstream economics. Moreover, MPV analyze the reported affiliation of each author listed in the Web of Science database and find that, in response to growing competition in the publishing process, economists tend to publish more in development studies journals. In this paper, I apply an alternative approach in identifying the disciplinary and paradigmatic background of development scholars by matching bibliometric data on articles published in World Development with the RePEc author database. The results from this analysis suggest a quite different picture regarding the share of economists that publish in the field's flagship journal: in contrast to MPV, I report a significantly higher share of scholars with an economics research background. Considering these findings, the paper further explores non-trivial differences of the "economics silo" (i.e. economists that publish research related to development) in World Development vis-à-vis research by scholars from other social science disciplines via extensive citation analysis. The overall finding of this analysis is that the lack of interdisciplinarity (as observed by MPV) is largely due to economists that publish their work in the journal.
Keywords: A14; O10; O29; O39; 330; Development; Interdisciplinarity; Citation Analysis; RePEc; Economic Imperialism